Make a Match Type of Cooperative Learning Model to Social Skills of Elementary School Students - Riyani, Eka Riyani; Rizal, Muhammad Syahrul; Ananda, Rizki; Mufarizuddin, Mufarizuddin; Aprinawati, Iis (Edumaspul: Jurnal Pendidikan, 2022)
This research was motivated by the low social skills of students during learning activities in class V SDN 020 Ridan Permai , Bangkinang City District, Kampar Regency. This study aims to improve students' social skills by using a make a match type of cooperative learning model in class V SDN 020 Ridan play . The type of this research is classroom action research which is carried out in two cycles. Each cycle consists of two meetings with four stages, namely planning, implementation, observation, and reflection. The subjects of this study were the fifth grade students of SDN 020 Ridan Permai , totaling 23 people, with 9 male students and 14 female students. The research data collection techniques are in the form of observation and documentation. The results of this research observation showed that the social skills of students in the first cycle there were 12 students in the complete category (52%). In the second cycle there was an increase to 19 students in the complete category (83%). Thus, it can be concluded that the application of the make a match type of cooperative learning model can improve the social skills of the fifth grade students of SDN 020 Ridan play .